2014
DOI: 10.1017/s1743921315002215
|View full text |Cite
|
Sign up to set email alerts
|

A survey of X-ray emission from 100 kpc radio jets

Abstract: Abstract. We have completed a Chandra snapshot survey of 54 radio jets that are extended on arcsec scales. These are associated with flat spectrum radio quasars spanning a redshift range z=0.3 to 2.1. X-ray emission is detected from the jet of approximately 60% of the sample objects. We assume minimum energy and apply conditions consistent with the original FeltenMorrison calculations in order to estimate the Lorentz factors and the apparent Doppler factors. This allows estimates of the enthalpy fluxes, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…EGRET has observed the source during its different pointed observations. Before the launch of Fermi, several studies were carried out to understand the γ-ray, X-ray, and UV/optical emission and spectral nature of PKS 0208-512 using the EGRET and other broad-band observations [43][44][45][46][47][48][49][50][51][52][53][54][55]. Using the EGRET and initial two years of Fermi-LAT observations, Bhattacharya et al [29] reported that PKS 0208-512 showed more than a factor of ten decrease in the average γ-ray flux from EGRET to Fermi era.…”
Section: Introductionmentioning
confidence: 99%
“…EGRET has observed the source during its different pointed observations. Before the launch of Fermi, several studies were carried out to understand the γ-ray, X-ray, and UV/optical emission and spectral nature of PKS 0208-512 using the EGRET and other broad-band observations [43][44][45][46][47][48][49][50][51][52][53][54][55]. Using the EGRET and initial two years of Fermi-LAT observations, Bhattacharya et al [29] reported that PKS 0208-512 showed more than a factor of ten decrease in the average γ-ray flux from EGRET to Fermi era.…”
Section: Introductionmentioning
confidence: 99%